Postpartum anoestrus interval and estrus activity in relation to postpartum body weight dynamics in indigenous and crossbred cows at Bako, Ethiopia - Gebreyohanes, Gebregziabher; Tegegne, Azage; Diedhiou, M.L.; Hegde, B.P. (2004)
Postpartum anoestrus interval (PPAI) and estrus activity measured as probability of getting acow in estrus within 42 (PPAI42), 63 (PPAI63) and 84 (PPAI84) days postpartum in indigenousand crossbred cows were studied using data from Bako Agricultural Research Center. PPAI wasanalyzed using the General Linear Model, while PPAI42, PPAI63 and PPAI84 were analyzedusing the Categorical Model Procedure of the Statistical Analysis System and LOGMLVARcomputer program. The results of the analysis indicated an overall least square mean PPAI of79.4 ± 1.99 days. Comparisons of the different genotypes, parities, calving seasons and yearsindicated that Boran x Simmental cross cows (136.9 ± 10.86 day), cows in the first parity (118.3 ±7.57 days), cows that calved during March to May (105.3 ± 5.78 days) and those that calved in1984 (128.3 ± 11.01 days) had significantly (P < 0.001) the longest PPAI. PPAI was significantly(P < 0.001) related to calving weight (b = -0.53 ± 0.14) and body weight gain from calving to threemonths (b= -0.04 ± 0.02). The overall mean predicted probability for PPAI42, PPAI63 and PPAI84were 0.33 ± 0.02, 0.53 ± 0.02 and 0.68 ± 0.02, respectively. Among the sire breeds, the Horro andJersey had significantly (at least P < 0.05) the highest PPAI42, PPAI63 and PPAI84 while as adam breed, the Horro had significantly (at least P < 0.01) higher PPAI42, PPAI63 and PPAI84than Boran cows. Cows in the later parities (5 to 6) had significantly (P < 0.05) highest PPAI42,PPAI63 and PPAI84 compared to cows in earlier parities (1-4). Calving weight showed asignificant (P < 0.001) effect on PPAI42, PPAI63 and PPAI84 and all those traits increased withincrease in calving weight. This study indicated the importance of calving weight and postpartumbody weight gain in affecting PPAI and estrus activity. Thus, improvement in these traits couldbe achieved through improvement of the calving weight and postpartum body weight gain.